Mapping the Green Economy in India: A Multi-Sectoral Conceptual Framework Integrating Technology, Sustainability, and Inclusive Growth (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The green economy has emerged as a transformative paradigm that reconciles environmental sustainability with economic growth and social equity. Despite India's ambitious commitments to net-zero emissions by 2070 and its rapidly expanding renewable energy sector, existing literature remains fragmented across individual industries, offering little integrative conceptual guidance. This article addresses that gap by developing a multi-sectoral conceptual framework that maps the architecture of India's green economy across twelve interrelated industry clusters. Drawing on conceptual synthesis and a systematic review of secondary literature, the study integrates Green Economy Theory, the Sustainable Development Framework, Circular Economy principles, Innovation Systems Theory, and Environmental, Social, and Governance (ESG) criteria into a unified analytical model. The framework identifies four functional layers—core productive sectors, enabling technology and finance sectors, circular and resource management systems, and social and inclusive drivers—and theorises the relational logic connecting them. The paper further discusses India-specific drivers, structural challenges, and policy implications. The findings contribute a replicable conceptual architecture applicable to large emerging economies navigating the sustainability transition, while providing a foundation for empirical validation and sector-specific research.